Blockchain-Based Cheat Detection System for Multiplayer Online Games - Arief, Syamsul Erisandy; Pamenang , Reyhan Fajar; Sari , Riri Fitri (Journal of Soft Computing and Data Mining, 2025)
The presence of competitive gaming in the video game industry requires a system that could promote fairness in the gameplay aspect. Many players have utilized networking attacks such as Distributed Denial of Service (DDoS) to win a competitive game. This action will enable players to gain an unfair advantage during gameplay. Attempts to cheat using DDoS attacks in competitive gaming created a significant need for a prevention mechanism. To satisfy this, we have designed a cheat detection system by leveraging Godot DotNet capabilities to connect a game client to the Ethereum Blockchain environment via Nethereum Web3 capabilities. Blockchain is used because it can keep records in an untampered state. We tested our system on the classic Pong game by capturing the positional data of all moving gameplay elements and sending them into the blockchain network. The location coordinate of each central gameplay element in the game is stored in the blockchain. The gameplay evaluation shows that 64-bit hex data of gameplay elements’ coordinates have been transmitted and stored successfully. The performance evaluation indicates that the game runs at 180 FPS using 6% of the GPU workload and 11% of the CPU workload, resulting in a time difference of under 200 ms for each transaction.